THERAPEUTIC POTENTIAL OF JAGGERY AGAINST SILICA NANOPARTICLES INDUCED TOXIC MANIFESTATIONS IN SPRAGUE-DAWLEY RATS - SUCHITA RAGHUVANSHI; SANGEETA SHUKLA (International Journal of Pharma and Bio Sciences, 2014)
The protective effects of aqueous extract of Jaggery were evaluated against silica nanoparticles (SNPs) induced toxic manifestations in liver, kidney and lung tissues. Male albino rats were orally treated with Jaggery (400 and 800 mg/kg) for 7 days, after intraperitoneal administration of SNPs (50 mg/kg) for 6 weeks. SNPs administration significantly increased the levels of serum alanine aminotransferase, aspartate aminotransferase, lactate dehydrogenase, serum alkaline phosphatase, urea, uric acid, creatinine and lipid peroxidation level in tissues, whereas substantial decreases were observed in levels of glutathione, alkaline phosphatase, glucose-6-phosphatase, superoxide dismutase, catalase enzymatic activities in liver, kidney & lung and albumin level in serum. Treatment of Jaggery has shown significantly restoration in the studied parameters toward normal value. Thus, Jaggery can be used to reduce tissues toxicity and may serve as an alternative medicine in the treatment of hepatic, renal and pulmonary tissues etiology.